Recurrent amebic liver abscesses over a 16-year period: a case report. (December 2016) - Creemers-Schild, D.; Genderen, P.; Visser, L.; Hellemond, J.; Wismans, P.
Abstract Background Amebic liver abscess is a rare disease in high-income countries. Recurrence of amebic liver abscess is even rarer with only a few previous reports. Here we present a patient who developed three subsequent amebic liver abscesses over a sixteen-year period. Case presentation A Caucasian male developed recurrent amebic liver abscesses, when aged 23, 27 and 39 years. Only on the first occasion did this coincide with a recent visit to the tropics. The patient received adequate treatment during each episode. Possible explanations are persistent asymptomatic carrier state, cysts passage in his family, re-infection or chance. Conclusion We describe the unusual case of a healthy male who developed recurrent amebic liver abscesses over a long period despite adequate treatment. Possible pathophysiological explanations are explored.